Discovering light. Introducing interference and diffraction - Costa, Manuel F. M. (2020)
Light plays a fundamental role in our lives and optics and photonics have a huge and ever increasing importance in a wide range of industries and impact in our modern societies. It is therefore essential that a solid knowledge on this subject is acquired as early as possible, right from primary school or even at kindergarten, in a process of active and participated discovery by the pupils themselves who naturally have an empathy, interest and special curiosity for this Light and Optics subject as it directly relates to vison, one of our major senses